2018
DOI: 10.1371/journal.pone.0201870
|View full text |Cite
|
Sign up to set email alerts
|

Using geographical analysis to identify child health inequality in sub-Saharan Africa

Abstract: One challenge to achieving Millennium Development Goals was inequitable access to quality health services. In order to achieve the Sustainable Development Goals, interventions need to reach underserved populations. Analyzing health indicators in small geographic units aids the identification of hotspots where coverage lags behind neighboring areas. The purpose of these analyses is to identify areas of low coverage or high need in order to inform effective resource allocation to reduce child health inequity bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 54 publications
3
39
1
2
Order By: Relevance
“…This disparity might be due to study sample size, study period, coverage of latrine and utilization, access to safe water for drinking. However, this nding is consistent with the ndings in other sub-Saharan and South Asian countries, a study in Tanzania and India [8,[33][34][35]. The results signify that the strategic approach of the government is fruitful and the sweats of focusing on low performing states are paying off.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This disparity might be due to study sample size, study period, coverage of latrine and utilization, access to safe water for drinking. However, this nding is consistent with the ndings in other sub-Saharan and South Asian countries, a study in Tanzania and India [8,[33][34][35]. The results signify that the strategic approach of the government is fruitful and the sweats of focusing on low performing states are paying off.…”
Section: Discussionsupporting
confidence: 89%
“…For example, according to the Global Burden of Disease study in 2016, 9.4% of all the severe cases of diarrhea in 2015 occurred in two countries: Ethiopia and the Democratic Republic of the Congo. In the Central African Republic, Gabon, Ivory Coast, Nigeria, and Zimbabwe saw disease increases over the 15 years [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to the Global Burden of Disease study in 2016, 9.4% of all severe cases of diarrhea in 2015 occurred in two countries, Ethiopia and the Democratic Republic of Congo. Also, diseases rise over 15 years have been seen in Central Africa, Gabon, Ivory Coast, Nigeria, and Zimbabwe [ 12 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, access to markets, healthcare facilities, communal education especially of women and young people is essential to improve nutritional levels in rural regions, generally improving access and social services would positively impact nutrition of children. Yourkavitch and colleagues found differences in health indicators in different geographic areas, and suggested that in order to improve health, these access differences needed to be addressed to reduce health inequalities (14). Others have also noted that an equity focused approach leading to improvement in effective intervention coverage results in sharp decreases in child mortality and stunting and higher cost-effectiveness (15).…”
Section: Discussionmentioning
confidence: 99%